Towards a conceptual framework for evaluating primary care research networks - Clement, S; Pickering, A; Thiru, K; Candy, B; de Lusignan, S; Rowlands, G (Royal College of General Practitioners, 2000)
We describe a conceptual framework that we have developed for evaluating primary care research networks. The framework includes objectives, process indicators, and outcome indicators. We propose the framework as a provisional model that we hope will promote further research and debate.